The Oxford handbook of wisdom and the Bible - Kynes, Will (Oxford handbooks online Religion, 2021)
This volume both reflects on the contested nature of the Wisdom Literature category and takes advantage of the opportunities it presents for reconsidering the concept of wisdom more independently from it. The first half explores wisdom as a concept, with essays on its relationship to skill, epistemology, virtue, theology, and order in the Hebrew Bible, its meaning in related cultures, from Egypt and Mesopotamia to Patristic and Rabbinic interpretation, and, finally, its continuing relevance in the modern world, including in Islamic, Jewish, and Christian thought, and from feminist, environmental, and other contextual perspectives. The latter half considers "Wisdom Literature" as a category. Scholars address its relation to the Solomonic Collection, its social setting, literary genres, chronological development, and theology.